Red blood cell hypoxanthine phosphoribosyltransferase activity measured using 6-mercaptopurine as a substrate: a population study in children with acute lymphoblastic leukaemia. - Lennard, L (1993)
1. 6-Mercaptopurine (6-MP) is used in the continuing chemotherapy of childhood acute lymphoblastic leukaemia. The formation of red blood cell (RBC) 6-thioguanine nucleotide (6-TGN) active metabolites, not the dose of 6-MP, is related to cytotoxicity and prognosis. But there is an apparent sex difference in 6-MP metabolism. Boys require more 6-MP than girls to produce the same range of 6-TGN concentrations. Given the same dose, they experience fewer dose reductions because of cytotoxicity, and have a higher relapse rate. 2. The enzyme hypoxanthine phosphoribosyltransferase (HPRT) catalyses the initial activation step in the metabolism of 6-MP to 6-TGNs, a step that requires endogenous phosphoribosyl pyrophosphate (PRPP) as a cosubstrate. Both HPRT and the enzyme responsible for the formation of PRPP are X-linked. 3. RBC HPRT activity was measured in two populations, 86 control children and 63 children with acute lymphoblastic leukaemia. 6-MP was used as the substrate and the formation of the nucleotide product, 6-thioinosinic acid (TIA) was measured. RBC 6-TGN concentrations were measured in the leukaemic children at a standard dose of 6-MP. 4. There was a 1.3 to 1.7 fold range in HPRT activity when measured under optimal conditions. The leukaemic children had significantly higher HPRT activities than the controls (median difference 4.2 micromol TIA ml(-1) RBCs h(-1), 95% C.I. 3.7 to 4.7, P < 0.0001). In the leukaemic children HPRT activity (range 20.4 to 26.6 micromol TIA ml(-1) RBCs h(-1), median 23.6) was not related to the production of 6-TGNs (range 60 to 1,024 pmol 8 x 10(-8) RBCs, median 323). RBC HPRT was present at a high activity even in those children with low 6-TGN concentrations. 5. When HPRT is measured under optimal conditions it does not appear to be the metabolic step responsible for the observed sex difference in 6-MP metabolism. This may be because RBC HPRT activity is not representative of other tissues but it could equally be because other sex-linked factors are influencing substrate availability.